2018
DOI: 10.1038/s41598-017-18871-0
|View full text |Cite
|
Sign up to set email alerts
|

Microdosimetric Modeling of Biological Effectiveness for Boron Neutron Capture Therapy Considering Intra- and Intercellular Heterogeneity in 10B Distribution

Abstract: We here propose a new model for estimating the biological effectiveness for boron neutron capture therapy (BNCT) considering intra- and intercellular heterogeneity in 10B distribution. The new model was developed from our previously established stochastic microdosimetric kinetic model that determines the surviving fraction of cells irradiated with any radiations. In the model, the probability density of the absorbed doses in microscopic scales is the fundamental physical index for characterizing the radiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 35 publications
7
70
0
Order By: Relevance
“…In a clinical study that was performed at Helsinki University Central Hospital [ 4 ], the results from two cohorts of patients receiving a differently planning tumor volume (PTV) dosing clearly showed that a small increase in the dose may lead to a much improved therapeutic outcome. The dose in BNCT, and in particular the “photon-equivalent”, “photon-isoeffective”, or “biologically weighted” [ 5 ] dose, is a key problem because the dose that the organs at risk may tolerate is a limiting factor in treatment planning and, therefore, it limits the dose delivered to PTV. Therefore, increasing the accuracy of the estimation of this dose can lead to an improvement of the clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In a clinical study that was performed at Helsinki University Central Hospital [ 4 ], the results from two cohorts of patients receiving a differently planning tumor volume (PTV) dosing clearly showed that a small increase in the dose may lead to a much improved therapeutic outcome. The dose in BNCT, and in particular the “photon-equivalent”, “photon-isoeffective”, or “biologically weighted” [ 5 ] dose, is a key problem because the dose that the organs at risk may tolerate is a limiting factor in treatment planning and, therefore, it limits the dose delivered to PTV. Therefore, increasing the accuracy of the estimation of this dose can lead to an improvement of the clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For the most widely used 10 B-based neutron capture agent, 10 B-4-borono-L-phenylalanine ( 10 B-BPA), CBE values of 3.6–3.8 and 0.9–1.3 have been reported for brain tumour cells and normal tissues, respectively, with tumour to healthy tissue concentration ratios between 5:1 and 8:1 16 , 20 23 . An alternative capture agent, borocaptate sodium (BSH), has shown potential for NCT applications; the reported range of CBE is between 1.2 and 2.3 in brain tumours and 0.37 to 0.5 in normal tissues, although the uptake concentration ratio tends to be much lower than for BPA (1.2–3.5 in the brain) 22 , 24 , 25 . The specific values differ for other target tissues, with higher values of CBE reported for liver tumours for both agents (tumour:liver CBE values of 9.94/4.25 and 4.22/0.94, and concentration ratios of 2.8/0.3 for BPA and BSH, respectively) 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Then, the user input parameters to our dosimetry system are α, β, and μ, which can be obtained from the measured surviving fractions of the reference radiation, as well as the fraction size X. Referring to our previous works [23,30], we set α = 0.251 Gy -1 , β = 0.0615 Gy -2 , μ = 1.5 h -1 and X = 2 Gy in the test simulations performed in this study. Consequently, EQDX(α/β) calculated in this study can be expressed as EQD2(4.08).…”
Section: Calculation Of Absorbed Doses Using Phitsmentioning
confidence: 99%
“…Under these situations, we developed a patient-speci c dosimetry system that can calculate EQDX(α/β) for TAT as well as other TRT, based on the Particle and Heavy Ion Transport code System (PHITS) [19] coupled with the microdosimetric kinetic model (MKM) [20]. The accuracy of RBE estimated by PHITS coupled with MKM was well veri ed for proton therapy [21], carbon-ion therapy [22], and boron neutron capture therapy (BNCT) [23]. In the system, a voxel phantom and a cumulative activity distribution map of a patient are automatically created in the PHITS input format from PET-CT images, respectively.…”
Section: Introductionmentioning
confidence: 99%